PENGARUH AKTIVITAS BELAJAR SISWA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR SISWA - Nisa Lathiva, Kayla; Januar Saputra, Henry; Sulianto, Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of students’ learning activity through the implementation of the Problem Based Learning (PBL) model assisted by Educaplay media on the learning outcomes of sixth-grade students at SDN 04 Kluwut Brebes. The study was motivated by the low learning outcomes of students in the Ilmu Pengetahuan Alam dan Sosial (IPAS) subject, where only 40% of students reached the minimum mastery criteria (KKM), allegedly caused by monotonous, teacher-centered learning that made students passive. This research used a quantitative method with an associative approach through simple linear regression analysis. The population and sample consisted of all 34 sixth-grade students (21 male and 13 female) of SDN 04 Kluwut, determined through saturated sampling. Data were collected through observation, interviews, a cognitive posttest, and documentation. The prerequisite tests showed that the data were normally distributed and linear. The simple linear regression analysis produced the equation Y = 1.106 + 1.012X with a significance value of 0.000 (p < 0.05) and a standardized coefficient (Beta) of 0.998, indicating a very strong and significant positive effect. It is concluded that the PBL model assisted by Educaplay media significantly improves students’ learning activity and learning outcomes.